KELAYAKAN FLASH CARD SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA KELAS X - Sri Oktaviani; Syamswisna Syamswisna; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2020)
This research aimed to test the feasibility of flashcard as learning media of The Benefit of Indonesian Biodiversity topic which discussed in 10th Grade of High School. This was qualitative research using a descriptive method. Two lecturers of the Biology Education Study Program of FKIP UNTAN and six Biology teachers from SMAN 1 Toba, SMAN 1 TayanHilir, and SMA YakotaTayanHilir participated in testing the media feasibility. Based on their evaluation, the flashcard was feasible to be used as the learning media in the Sub Material of the Benefit of Indonesian Biodiversity, with the CVR value of 0,78 according to the Lawshe CVR and CVI value for 8 evaluators.